Fresno County Young Lawyers Association Justice George Hopper Memorial Luncheon at Star Palace - Watkins, Howard::::::::: (1982)
Fresno County Young Lawyers Association President John McGregor seated with keynote speaker Justice Stanley Mosk and Judge Leonard Meyers